Identification of coronaviruses in farmed wild animals reveals their evolutionary origins in Guangdong, southern China. Issue 1 (21st June 2022) - Wang, Xiaohu; Ren, Zhaowen; Wang, Lu; Chen, Jing; Zhang, Pian; Chen, Jin-Ping; Chen, Xiaofan; Li, Linmiao; Lin, Xuhui; Qi, Nanshan; Luo, Shengjun; Xiang, Rong; et al.
Abstract: Coronavirus infections cause diseases that range from mild to severe in mammals and birds. In this study, we detected coronavirus infections in 748 farmed wild animals of 23 species in Guangdong, southern China, by RT-PCR and metagenomic analysis. We identified four coronaviruses in these wild animals and analysed their evolutionary origins. Coronaviruses detected in Rhizomys sinensis were genetically grouped into canine and rodent coronaviruses, which were likely recombinants of canine and rodent coronaviruses. The coronavirus found in Phasianus colchicus was a recombinant pheasant coronavirus of turkey coronavirus and infectious bronchitis virus. The coronavirus in Paguma larvata had a high nucleotide identity (94.6–98.5 per cent) with a coronavirus of bottlenose dolphin ( Tursiops truncates ). These findings suggested that the wildlife coronaviruses may have experienced homologous recombination and/or crossed the species barrier, likely resulting in the emergence of new coronaviruses. It is necessary to reduce human–animal interactions by prohibiting the eating and raising of wild animals, which may contribute to preventing the emergence of the next coronavirus pandemic.